The Strategic Role of Human Resource Management in Improving the Performance of Educational Organizations: A Literature Review - Sa’adah, Masrurotus; Dui, Risda; Nikmah, Tiara Iftitahun; Auldina, Betha; Sa’adah, Musdalifatus; Amalia, Novi Nur; Mualimin, Mualimin (Aksara Shofa, 2025)
This article aims to explore the role of Human Resource Management (HRM) in improving the performance of educational organizations through a literature review. The research method used is a literature review by collecting and analyzing relevant sources from academic databases such as Google Scholar and Scopus. The research results show that effective planning, development, and evaluation of human resources are the main keys to improving the performance of educational organizations. HR planning involves needs analysis, competency development, and adaptation to environmental changes. HR development focuses on training, motivation, and the formation of a collaborative organizational culture. Meanwhile, HR evaluation helps in identifying strengths and weaknesses in performance and in developing relevant development programs. The main challenges include global competition, technological advancements, and the demand for quality education. This article provides strategic recommendations for educational institutions to manage human resources holistically in order to achieve better organizational goals